2022
DOI: 10.3390/ijerph19116889
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Education in Preventing Unhealthy Lifestyles in Immigrant Adolescents

Abstract: In recent years, migratory phenomena have changed the composition of Spanish society. There are many studies that explore the healthy habits of young adolescents, but few focus on young immigrants. The purpose of this study is to examine the causal relationships between certain factors that influence the health of immigrant youth and sports. The sample consisted of 173 students enrolled in secondary education in the city of Cuenca. The structural model confirms the relationship between the latent variables and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…We have confirmed that combining psycho-training practical classes and health fitness training classes helps to achieve positive changes in female students' physical and psycho-emotional state, which is consistent with previous research that indicates a relationship between physical activity, psychological well-being and health status (Mondéjar-Jiménez et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have confirmed that combining psycho-training practical classes and health fitness training classes helps to achieve positive changes in female students' physical and psycho-emotional state, which is consistent with previous research that indicates a relationship between physical activity, psychological well-being and health status (Mondéjar-Jiménez et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Our research does not contradict the results obtained by other scientists (Yarmak et al, 2017;Mondéjar-Jiménez et al, 2022;Lacoste et al, 2020;Carter-Thuillier et al, 2022). Many previous studies have confirmed the importance of physical activity and psychological well-being for overall health and well-being (Poblete-Valderrama et al, 2023;Galan et al, 2023).…”
Section: Discussionsupporting
confidence: 80%